The IOC Centres of Excellence bring prevention to Sports Medicine - Engebretsen, L.; Bahr, R.; Cook, J. L.; Derman, W.; Emery, C. A.; Finch, C. F.; Meeuwisse, W. H.; Schwellnus, M.; Steffen, K. (British Journal of Sports Medicine, 2014)
The protection of an athlete`s health and preventing injuries and illnesses in sport are top priorities for the IOC and its Medical Commission. The IOC therefore partners with selected research centres around the world and supports research in the field of sports medicine. This has enabled the IOC to develop an international network of expert scientists and clinicians in sports injury and disease prevention research. The IOC wants to promote injury and disease prevention and the improvement of physical health of the athlete by: (1) establishing long-term research programmes on injury and disease prevention (including studies on basic epidemiology, risk factors, injury mechanisms and intervention), (2) fostering collaborative relationships with individuals, institutions and organisations to improve athletes` health, (3) implementing and collaborating with applied, ongoing and novel research and development within the framework and long-term strategy of the IOC and (4) setting up knowledge translation mechanisms to share scientific research results with the field throughout the Olympic Movement and sports community and converting these results into concrete actions to protect the health of the athletes. In 2009, the IOC also identified four research centres that had an established track record in research, educational and clinical activities to achieve these ambitions: (1) the Australian Centre for Research into Injury in Sport and its Prevention (ACRISP), Australia; (2) the Sport Injury Prevention Research Centre (SIPRC), Canada; (3) the Clinical Sport and Exercise Medicine Research (CSEM), South Africa and (4) the Oslo Sports Trauma Research Center (OSTRC), Norway. This paper highlights the work carried out by these four IOC Centres of Excellence over the past 6 years and their contribution to the world of sports medicine.